Firm money in the approach to shariah economic law - Nurnafilah, Hikmahtian; Kurniawati, Fitri (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2024)
The swift and unprecedented progress of scientific inquiry and technological innovation in the contemporary digital landscape has ushered in transformative and revolutionary shifts in the realm of financial transactions, whereby individuals no longer find it necessary to endure the tedious process of queuing in order to establish a savings account or to bide their time awaiting the issuance of an ATM card; instead, in this modern age, all that is required is the simple act of downloading an application and replenishing one’s balance, which facilitates immediate transactional capabilities. The outcomes derived from the comprehensive analysis indicate that the four electronic money platforms, namely BCA Sakuku, Link Aja, OVO, and GoPay, serve as significant representatives of their growing presence within the Indonesian market, warranting not only heightened scrutiny from regulatory authorities but also necessitating an in-depth examination from the perspective of Islamic jurisprudence, especially considering that a substantial proportion of the users engaging with these electronic monetary systems identify as Muslim. The emergence and proliferation of electronic money is an undeniable phenomenon that cannot be dismissed or overlooked, as it is intrinsically linked to the rapid pace of technological advancement, compelling the legal framework to adapt and align itself with the exigencies of progress inherent in this millennial epoch characterized by digitalization, speed, and precision; it is conceivable that physical currency may, in certain contexts, be rendered obsolete.